2022
DOI: 10.3390/ijms23020886
|View full text |Cite
|
Sign up to set email alerts
|

Validating Reference Gene Expression Stability in Human Ovarian Follicles, Oocytes, Cumulus Cells, Ovarian Medulla, and Ovarian Cortex Tissue

Abstract: Human ovarian cells are phenotypically very different and are often only available in limited amounts. Despite the fact that reference gene (RG) expression stability has been validated in oocytes and other ovarian cells from several animal species, the suitability of a single universal RG in the different human ovarian cells and tissues has not been determined. The present study aimed to validate the expression stability of five of the most used RGs in human oocytes, cumulus cells, preantral follicles, ovarian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Several previous studies have been using GAPDH as a reference gene. According to Cadenas, J et al ( 2022), GAPDH was found to be the most stable gene for this type of tissue [20]. Also, according to Nikishin et al, they found that levels of GAPDH, ACTB, and HSP90 proteins are similar in native and vitrified/thawed ovarian samples [21].…”
Section: Rna Isolation Cdna Synthesis and Qrt-pcrmentioning
confidence: 97%
“…Several previous studies have been using GAPDH as a reference gene. According to Cadenas, J et al ( 2022), GAPDH was found to be the most stable gene for this type of tissue [20]. Also, according to Nikishin et al, they found that levels of GAPDH, ACTB, and HSP90 proteins are similar in native and vitrified/thawed ovarian samples [21].…”
Section: Rna Isolation Cdna Synthesis and Qrt-pcrmentioning
confidence: 97%
“…Previous studies have reported relatively high variability for the expression of WU-HKGs in a varied range of tissues and organs in livestock animals ( Gromboni et al, 2020 ; Lozano-Villegas et al, 2021 ) as well as in humans ( Mahoney et al, 2004 ; Caracausi et al, 2017 ; Cadenas et al, 2022 ), mice ( Fu et al, 2020 ; Muñoz et al, 2021 ), and insects ( Shi et al, 2016 ), among others.…”
Section: Resultsmentioning
confidence: 99%
“…They suggested the combination of Ywhaz , Hprt1 , and Hmbs as the best set of reference genes for ovarian and uterine tissues of laying hens under control and heat stress conditions. Cadenas et al (2022) found that the stability of all reference genes differs among ovarian cell types in humans. They identified Actb as the best reference gene for oocytes and cumulus cells and B2m for medulla tissue and isolated follicles.…”
Section: Resultsmentioning
confidence: 99%
“…Predesigned TaqMan® gene expression assays were performed using following genes: Murine Vascular Endothelial Growth Factor Alpha ( Vegfα), Angiopoietin 1 (Angpt1), Angiopoietin 2 ( Angpt2), Angiopoietin-like 4 (Angptl4) and human B-Cell Lymphoma 2 (BCL2) and BCL-2 associated X protein (BAX), (probe-id: Vegfα, Mm00437306_m1; Angpt1, Mm00456503_m1; Angpt2, Mm00545822_m1; Angptl4, Mm00480431_m1; BCL2 , Hs00608023_m1; BAX , Hs00180269_m1). Glyceraldehyde 3-phosphatdehydrogenase ( Gapdh/GAPDH ) was used as endogenous control for both murine and human gene expression assays [ 44 ] (probe-id: GAPDH, Hs 02786624_g1 ; Gapdh, Mm99999915_m1). The cDNA samples were amplified in duplicates using the LightCycler®480 quantitative PCR instrument (Roche, version 1.5.0.39) as previously described [ 21 , 26 ].…”
Section: Methodsmentioning
confidence: 99%